Pengaruh Motivasi, Kompensasi, dan Budaya Organisasi Terhadap Kinerja Karyawan pada PT. Pos Indonesia (Persero) Padang - Astuti, Annisa Yulia; Salfadri; Yulistia (Fakultas Ekonomi, Universitas Ekasaktii, 2023)
This research aims to identify dominant indicators in the variables of employee performance, motivation, compensation, and organizational culture at PT. POS Indonesia (Persero) Padang and to see the influence of motivation, compensation, and organizational culture partially and jointly on employee performance at PT. POS Indonesia (Persero). Research data using primary data was obtained by distributing questionnaires to employees of PT. Pos Indonesia Padang branch on the street. Bagindo Aziz Chan, numbering 78 people. The technique for data analysis uses multiple linear regression, t-test, and F then the coefficient of determination. The research results include (1) The dominant indicator in the motivation variable is the need for security with an average of 4.20 with a TCR of 84.00%. The dominant indicator in the compensation variable is allowances with an average of 4.22 with a TCR of 84.40%. The dominant indicator of organizational culture is performance with an average of 4.10 and a TCR of 82.00%. The dominant indicator of employee performance is work quantity with an average of 4.21 and TCR of 84.20%.